Parenting Style Practice as an Effort to Optimize Children's Social-Emotional, Psychosexual Development - Elly Dwi Masita; Uke Maharani Dewi; Hinda Novianti; Annif Munjidah (Community Development Journal)
Sidoarjo is one of the number 3 highest cities related to the prevalence of sexual violence with 8,701 cases from 2020 to 2023. Sidoarjo is an area prone to sexual violence committed by the family itself because the perpetrator is in the realm of economic inequality.  A survey conducted in December 2023 found that 82% of parents do not understand social-emotional and psychosexual development, 93% do not understand parenting models, 87% have never attended parenting seminars or training, 89% do not know the consequences of delayed social-emotional and psychosexual development, 97% do not understand that the support of the community and the surrounding environment provides stimulus to these two developments. This activity aims to provide knowledge and skills to parents related to parenting models to optimize children's social-emotional and psychosexual development by using a paeticypatory approach  building approach model through demonstrations and role-play towards 50 parents who has   child in 1- 5 years old. The activity method is a participatory approach through learning classes, parenting model exercises and role models. Data colected to use Observation Checklists to Develop a checklist of key participatory elements and observe meetings or events to assess their presence. Based on graph 1.1, it was found that there was an average increase in knowledge scores of 67.5% and skill scores of 72%. Participatory approaches are highly effective in increasing the relevance and ownership of community services. By actively involving community members in the planning and implementation of initiatives, these approaches empower individuals, enhance the relevance of services, and promote sustainable outcomes